The challenges of economic and institutional reforms in Africa - Saitoti, George (Aldershot ; Burlington, VT : Ashgate, 2002)
This work identifies how to create a climate conducive to economic takeoff and focuses on the specific challenges faced by Africa. Essentially, private and political commitment along with international help to move from aid dependency to an aid "exit strategy" are the key.
Includes bibliographical references (p. 355-362) and index.
oif 06/11/15
Loan
Keywords: Africa; Africa; Africa